KINEMATICS OF THE WORKING BODIES OF THE MECHANISM OF THE HINGE COUPLING AT DIFFERENT VALUES OF THE NUMBER OF INPUT LINK SPEEDS - Toshov Buri Radjabovich; Hamroyev Sherzod Gulmurotovich (Web of Journals Publishing, 2024)
The laws of motion of the working bodies, consisting of three output links at different numerical values of the revolutions of the input link, are experimentally determined, and an interpolation cubic spline function of the law of motion is found using the Mathcad program. The first of the three working bodies is the output half-coupling, which circulates the liquid. The first-order numerical derivative obtained from its law of motion, that is, the variability of the angular velocity of the output half-coupling in one period shows that it operates in a non-stationary mode. The second and third output working links, consisting of telescopic rods, transmit rotational motion from the input link of the mechanism to the output link of the coupling half through the reciprocating movement of its piston, and at the same time act as a piston pump, accelerating the process of mixing the liquid, sucking and pumping them.
Keywords: articulated clutch, structural diagram, mechanism model, input and output links, law of motion, regression, angular velocity, gear ratio.